Efficacy and toxicity of re-irradiation spine stereotactic body radiotherapy with respect to irradiation dose history. (6th October 2020) - Ito, Kei; Ogawa, Hiroaki; Nakajima, Yujiro
Abstract: Objective: We aimed to clarify the outcomes of re-irradiation stereotactic body radiotherapy for spinal metastases with a uniform dose fractionation schedule at our institution. Methods: Data of patients treated with re-irradiation stereotactic body radiotherapy for spinal metastases (September 2013–March 2020) were retrospectively reviewed. The prescribed dose was 24 Gy in two fractions. The spinal cord dose constraint and dose for previously irradiated cases ≥50 Gy in 25 fractions were 12.2 Gy (maximum dose) and 11 Gy, respectively. The endpoints were pain control, local failure and adverse effects. Pain status was measured on a scale of 0–10 using the patients' self-reports and pain response was defined using international consensus criteria. Local failure was defined as tumor progression on imaging evaluations. Results: We assessed 133 lesions in 123 patients, where 70 (52.6%) had three or more spinal levels treated, 58 (43.6%) had previous irradiation doses of 40 Gy or more and 53 (39.8%) had the targets compressing the cord. The median follow-up was 12 months and the 3-, 6- and 12-month pain response rate was 75, 64 and 59%, respectively. The 1-year local failure rate was 25.8%. Previous irradiation dose was not correlated with local failure rate ( P = 0.13). Radiation-induced myelopathy, radiculopathy and vertebral compression fractures were observed in 4 (3.0%), 2 (1.5%) and 17 (13.8%) lesions, respectively. A trend towards an association between any toxicity and previous irradiation dose was not observed. Conclusions: Re-irradiation spine stereotactic body radiotherapy achieved good local control and pain control, with reduced risk of radiation myelopathy. Abstract : We demonstrated good local control and pain control in patients who received re-irradiation stereotactic body radiotherapy for spinal metastases, with a clinically acceptable safety profile.